Characterising mesoscale variability in low-level jet simulations for CBLAST-LOW 2001 campaign - Tay, Ken; Koh, Tieh-Yong; Skote, Martin (Springer, 2020)
A low-level jet (LLJ) event observed during a frontal passage in the 2001 Coupled Boundary Layers and Air–Sea Transfer Experiment in Low Winds campaign was simulated using the Weather Research and Forecasting model (WRF). The sensi-tivity of the modeled LLJ characteristics, such as formation time, height and the strength of the LLJ core, to the choice of initial and boundary conditions, planetary boundary layer (PBL) schemes and vertical resolution was evaluated with a suite of diagnostic tools. The model simulations were compared against available soundings from the campaign observations as well as with surface observations from the Automated Surface Observing Systems. The simulation initialized with ERA-interim reanalysis and using the Mellor–Yamada–Nakanishi–Niino PBL scheme gave the best mix of diagnostic scores for surface temperature and wind speed predictions. The choice of boundary conditions introduced a stronger variability in the LLJ characteristics than the changes in PBL schemes or vertical resolution. The variability emerged primarily due to the timing of the frontal passage in the boundary condition datasets.
Keywords: Diagnostic suite; Offshore wind resource assessment; WRF; Low-level jet